DIFFERENCES IN LANGUAGE DEVELOPMENT IN MORPHOLOGICAL ASPECTS IN CHILDREN WITH INTROVERTED AND EXTROVERTED PERSONALITY TYPES - Wulandari, Triana Rahma; Karunia Putra, Dona Aji (JURNAL KONFIKS, 2025)
This study is motivated by the importance of understanding the relationship between personality traits and children's language development, particularly in the area of morphology. The aim of this research is to describe the differences in morphological development in eight-year-old girls with introverted and extroverted personality types. This study employs a qualitative approach using a descriptive method. The research subjects consist of three girls: two with introverted personalities and one with an extroverted personality. All three subjects are students at a public elementary school located in the Kranggan area, Bekasi City. Data were collected through observation, interviews, and documentation, using image-based stimuli designed to elicit written linguistic responses. The primary data consist of the children’s written texts, which were analyzed with a focus on their acquisition of morphological forms, including prefixes, suffixes, circumfixes, and reduplications. The findings show that the three subjects produced a total of 340 affixes, comprising 91 prefixes, 12 suffixes, 61 circumfixes, and 23 reduplications. The differences in personality types appear to influence the variation and quantity of morphological forms used by each child. Theoretically, this research contributes to psycholinguistic studies, particularly in exploring how psychological factors affect language development. Practically, the findings can be utilized by teachers, speech therapists, and parents as a foundation for designing language learning strategies that are tailored to the child’s personality traits in order to optimize their linguistic potential.